2020
DOI: 10.1002/pmrj.12429
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and Clinical Analyses of Autologous Bone Marrow Aspirate Injectate for Knee Osteoarthritis: A Pilot Study

Abstract: Introduction Knee osteoarthritis (OA) is characterized by pain and functional deficits. Common conservative strategies include medications, physical therapy, and intra‐articular injections. Recently, treatment using autologous cell injections has increased. Objective To characterize the cellular content of bone marrow aspirate (BMA) and to evaluate the effect of intra‐articular autologous BMA injections in patients with mild knee OA. Design Prospective pilot observational study. Setting Academic institution. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(49 citation statements)
references
References 33 publications
1
47
0
Order By: Relevance
“…After anesthetization of the target site, 10,000 units/mL heparin were withdrawn into a 10-mL syringe, and after the syringe was connected to the introducer needle, heparin was injected until the introducer needle was fully rinsed and then aspirated back into the syringe. All 8 studies 2,14,28,34,39,40,43,47 described aspirating bone marrow from the posterior superior or anterior superior iliac spine. After sterile skin preparation, draping, and local anesthesia, the access needle was inserted into the medullary space, and 12 to 120 mL of BMAC was aspirated while withdrawing and rotating the needle.…”
Section: Resultsmentioning
confidence: 99%
“…After anesthetization of the target site, 10,000 units/mL heparin were withdrawn into a 10-mL syringe, and after the syringe was connected to the introducer needle, heparin was injected until the introducer needle was fully rinsed and then aspirated back into the syringe. All 8 studies 2,14,28,34,39,40,43,47 described aspirating bone marrow from the posterior superior or anterior superior iliac spine. After sterile skin preparation, draping, and local anesthesia, the access needle was inserted into the medullary space, and 12 to 120 mL of BMAC was aspirated while withdrawing and rotating the needle.…”
Section: Resultsmentioning
confidence: 99%
“…The available results of these trials indicated both BMAC and SVF were safe and therapeutic for OA applications. 20 , 21 , 54 - 57 …”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of clinical trials is a prerequisite for further clinical applications. Clinical trials focusing on the potential of stem cells in cartilage regeneration have also been carried out ( Wells et al, 2020 ). Some types of stem cells have already entered clinical trials, among which the hUCB-MSC-based therapeutic product CARTISTEM has been approved by the Korean FDA for marketing.…”
Section: Introductionmentioning
confidence: 99%